Comparison of The Effectiveness Between Propolis and Silver Sulfadiazine 1% on Burn Wound Healing - I Ketut Sudiana; Walida Pangestuti; Wahyuni Tri Lestari (Universitas Airlangga, 2009)
Introduction: Silver sulfadiazine 1% is often used as topical agent in burn wound due to its antimicrobial effect. Moreover, this agent has toxigenic effect on fibroblast and keratinocyte. Propolis is a honey bee product and has been used for a long time in burn wound related to antimicrobial effect, anti-inflammation, anti-oxidant and increasing fibroblast. The purpose of this study was to examining the differences between propolis and silver sulfadiazine 1% on burn wound healing process. Method: Design used in this study was true experimental design. The samples were 18 guinea pigs divided randomizely into three group. The groups were control group, propolis group, and silver sulfadiazine group. The independent variables were the using of propolis and silver sulfadiazine 1%. The dependent variables were inflammation phase (erythema, oedema, wound fluid) and proliferation phase (wound granulation, wound size) which were observed on the 3rd, 7th, 14th days. Data were collected by using observation paper based on the sign of inflammation and proliferation. Data were analyzed using One-Way ANOVA and Kruskal-wallis test with level of significance of α ≤ 0.05. Result: Results showed that there were differences between propolis and silver sulfadiazine 1% in erythema (p=0.00) and oedema (p=0.001) on 3rd day and erythema (p=0.00) and oedema (p=0.00) on7th day, furthermore burn wound size (p=0.00) on14th day was also attenuated by propolis and silver sulfadiazine 1 %. It can be concluded that the using of propolis was more effective than silver sulfadiazine 1% in burn wound healing. Discussion: Further studies involved microscopic observation of collagen, PMN cell (neutrophile), lymphocyte and monocyte cell are needed.